Increased profitability of open pit mining operations by elimination of over-drilling - Ortiz Sánchez, Oswaldo (2008)
The Sub drilling length in surface mining production drilling grids, can be reduced or eliminated by addition of air chambers at the bottom of drill holes in blasting rounds. Sub drilling removal means surface mine operations revenue increase due to lower drilling and blasting costs, seismic vibrations decrease at inside and outside excavation areas, stable berms and slopes, productivity increase of drilling, loading, excavation, haulage and primary crushing equipment due to better ore fragmentation. The method was satisfactorily tested in a medium hardness rock at a quarry operation.